2007
DOI: 10.1534/genetics.106.069914
|View full text |Cite
|
Sign up to set email alerts
|

Essential, Overlapping and Redundant Roles of the Drosophila Protein Phosphatase 1α and 1β Genes

Abstract: Protein serine/threonine phosphatase type 1 (PP1) has been found in all eukaryotes examined to date and is involved in the regulation of many cellular functions, including glycogen metabolism, muscle contraction, and mitosis. In Drosophila, four genes code for the catalytic subunit of PP1 (PP1c), three of which belong to the PP1a subtype. PP1b9C (flapwing) encodes the fourth PP1c gene and has a specific and nonredundant function as a nonmuscle myosin phosphatase. PP1a87B is the major form and contributes $80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 40 publications
1
37
0
1
Order By: Relevance
“…A knockdown approach was not an attractive option because of the redundancy between PP1 isoforms, which enables PIPs to form functional complexes with other PP1 isoforms once their preferred isozyme is removed (Gibbons et al, 2007;Kirchner et al, 2007;TrinkleMulcahy et al, 2006;Varmuza et al, 1999). In addition, none of the available small-molecule, cell-permeable inhibitors of PPP-type phosphatases is specific for PP1, making a chemical genetics approach unfeasible (De Munter et al, 2013;Gehringer, 2004;Kelker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A knockdown approach was not an attractive option because of the redundancy between PP1 isoforms, which enables PIPs to form functional complexes with other PP1 isoforms once their preferred isozyme is removed (Gibbons et al, 2007;Kirchner et al, 2007;TrinkleMulcahy et al, 2006;Varmuza et al, 1999). In addition, none of the available small-molecule, cell-permeable inhibitors of PPP-type phosphatases is specific for PP1, making a chemical genetics approach unfeasible (De Munter et al, 2013;Gehringer, 2004;Kelker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Another problem stems from the functional redundancy between PP1 isoforms, making knockdown experiments of individual isoforms rather uninformative (Cheng et al, 2000;Kirchner et al, 2007;Trinkle-Mulcahy et al, 2006;Varmuza et al, 1999). We have delineated the global role of PP1 in cell cycle progression using cell lines that inducibly overexpress nuclear inhibitor of PP1 (NIPP1; also known as PPP1R8).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila , PP1 is found at multiple sites on chromosomes where it has been postulated to play important roles in regulating developmentally controlled gene expression [17], [18]. However, analysing the role of PP1 in transcriptional regulation has been complicated by its pleiotropic roles [19] and broad in vitro substrate specificity. In vivo , PP1 has been shown to associate with different targeting subunits that restrict its activity towards particular substrates [20].…”
Section: Introductionmentioning
confidence: 99%
“…We cannot exclude a role for other related targeting subunits such as Mypt2, Mypt3 and TIMAP (reviewed in 5) or yet other unidentified targeting subunits, and a further analysis of PP1 binding proteins in early development may be warranted. Additionally, given the considerable functional redundancy between PP1 isoforms observed in other organisms [15,3335], it could be quite informative to characterize overlapping functions with other zebrafish PP1 genes such as ppp1caa , ppp1cab and ppp1cc . Such an analysis may uncover additional roles for ppp1cba and ppp1cbb .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, zebrafish have five PP1 genes: two genes similar to PP1α, two genes similar to PP1β and one gene related to PP1γ. Genetic experiments in flies and mice have indicated that PP1 isoforms have both unique isoform-specific functions and other roles that overlap with the other PP1 isoforms [33,34]. While all three mammalian PP1 isoforms can partially complement the single essential PP1 catalytic subunit in S.…”
Section: Introductionmentioning
confidence: 99%